2022
DOI: 10.1093/mnras/stac2747
|View full text |Cite
|
Sign up to set email alerts
|

SN 2020wnt: a slow-evolving carbon-rich superluminous supernova with no O ii lines and a bumpy light curve

Abstract: We present the analysis of SN 2020wnt, an unusual hydrogen-poor super-luminous supernova (SLSN-I), at a redshift of 0.032. The light curves of SN 2020wnt are characterised by an early bump lasting ∼5 days, followed by a bright main peak. The SN reaches a peak absolute magnitude of M$_{r}^{max}=-20.52\pm 0.03$ mag at ∼77.5 days from explosion. This magnitude is at the lower end of the luminosity distribution of SLSNe-I, but the rise-time is one of the longest reported to date. Unlike other SLSNe-I, the spectra … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 156 publications
1
9
0
Order By: Relevance
“…It is present in the premaximum of 26 examined and can be characterized with a temperature between 12,000 and 15,000 K (Inserra 2019). In accordance with this finding, the T phot values of Type 15bn SLSNe-I were found to be smaller or equal to 12,000 K, while Type W objects were modeled applying larger temperatures, in some cases even exceeding 15,000 K. Gutiérrez et al (2022) studied the A lower (T phot = 13,000 K) and a higher (T phot = 17,000 K) model is plotted as well with green and blue colors, respectively. The three models share the same global and local parameters with the exception of the photospheric temperature.…”
Section: Temperature/ion Compositionsupporting
confidence: 70%
See 3 more Smart Citations
“…It is present in the premaximum of 26 examined and can be characterized with a temperature between 12,000 and 15,000 K (Inserra 2019). In accordance with this finding, the T phot values of Type 15bn SLSNe-I were found to be smaller or equal to 12,000 K, while Type W objects were modeled applying larger temperatures, in some cases even exceeding 15,000 K. Gutiérrez et al (2022) studied the A lower (T phot = 13,000 K) and a higher (T phot = 17,000 K) model is plotted as well with green and blue colors, respectively. The three models share the same global and local parameters with the exception of the photospheric temperature.…”
Section: Temperature/ion Compositionsupporting
confidence: 70%
“…This discovery allowed Nicholl et al (2016b) to suggest that such bumps may be usual/omnipresent features in SLSNe-I; however, this theory was refuted by Angus et al (2019), who carried out a detailed analysis of SLSNe-I from the Dark Energy Survey and found that only three SLSNe-I showed early bumps in their sample of 14 objects. Later on, PFT12dam (Vreeswijk et al 2017), and potentially SN 2018bsz (e.g., Anderson et al 2018;Chen et al 2021;Gutiérrez et al 2022;Pursiainen et al 2022) and SN 2018hti (Lin et al 2020;Fiore et al 2022) were revealed to show early LC undulations. Gutiérrez et al (2022) examined this topic in detail and found that some SLSNe-I that show smooth LC in their early phase can be characterized by slow photometric evolution (e.g., SN 2007bi, Gal-Yam et al 2009Young et al 2010;LSQ14an, Inserra et al 2017;SN 2015bn, Nicholl et al 2016a, 2016bSN 2017gci, Fiore et al 2021 in their sample).…”
Section: Premaximum Light-curve Undulationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Including the Sc II features improved the fitting between 4000 and 6000 Å, even though Sc is not commonly identified in SN Ic spectra. Recently, Gutiérrez et al (2022) also found Sc II in spectra of SN 2020wnt, a peculiar hydrogen-poor Type I SLSN. Since SLSN-I spectra are somewhat similar to those of SNe Ic, the presence of Sc II is not unexpected.…”
Section: Optical Spectral Modeling: Photospheric Phasementioning
confidence: 91%